The Participation between Indigenous Empowerment and State Normalization - Cherñavsky, Sasha Camila (2024)
The present work starts from a social and systematic anthropological perspective with its epistemological limitations and openings with a constant analytical and methodological deconstruction within the framework of critical and reflexive practices. We will seek to understand the dynamics and implications of the normative, historical and structural relations between the State and indigenous peoples in two working spaces: the Provincial Council of Indigenous Affairs (CPAI) located in La Plata, and the comanagement in Bariloche located within the National Parks Administration (APN). Therefore, we will investigate and analyze a heterogeneous corpus that includes legal and administrative materials composed of a particular language and logic of state bureaucracy. In this context, we will observe these dynamics and tensions through the legal personality as a case of analysis of such strategic uses by indigenous people to reaffirm themselves as communities and, at the same time, this process translated into a normative “waiting” as a control mechanism. This will allow us to understand the historical, normative and structural relations with the State and participation as the main dimension of work.